Methodological Aspects of Employing a Competency-Based Approach within the System of Management of Public Procurement: International Experience - GLADILINA, Irina Petrovna; POGUDAEVA, Marina Yur'evna; POLOVOVA, Tat'yana Aleksandrovna; SERGEEVA, Svetlana Alexandrovna; LOTVINA, Ol'ga Vladimirovna (Journal of Advanced Research in Law and Economics, 2018)
Over the course of several decades, international practice in the area of development of the institution of public procurement has produced a number of uniform approaches to cultivating relevant competencies in managers at public procurement agencies with a view to enhancing their management skills. Monitoring the outcomes of procurement activity enables various nations around the world to resolve the issue of establishing the optimum number and line-up of public contracting specialists based on the analysis of their qualification levels, experience, and theoretical training. Concurrently, relevant research is conducted into the quality of education in public procurement (training courses; career enhancement and professional retraining programs). Public procurement practice has proven the necessity of having in place a long-term policy for enhancing the skills of managers and specialists employed within the procurement sector.